Implementasi Manajemen Berbasis Sekolah dalam Penguatan Pendidikan Karakter di MTsN 3 Siak - Abdullah, Abdullah; Safitri, Yuni; Suherman, Suherman; Erlisnawati, Erlisnawati (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study is to explain and analyse how the implementation of school-based management (SBM) helps improve character education at MTsN 3 Siak. This study was conducted using a qualitative and case study approach. There were seven teachers, one madrasah head, nine students from grades VII, VIII, and IX, and two parents (madrasah committee). Participatory observation, documentation, and in-depth and thorough interviews were the data collection methods used in this study. Data analysis techniques used the Miles and Huberman model with the steps of data reduction, data presentation, and conclusion drawing. Triangulation of sources, techniques and time was used to ensure accurate data. The results showed that the implementation of MBS at MTsN 3 Siak went well enough to improve character education through madrasah policies, extracurricular activities, exemplary teachers, and parental participation. Nevertheless, there are still some barriers, such as resistance to change and limited resources. This research shows that training of principal managers and increasing whole-school participation in character strengthening are essential.